Hydrolytic and oxidative degradation of electrospun supramolecular biomaterials: In vitro degradation pathways. (November 2015) - Brugmans, M.C.P.; Sӧntjens, S.H.M.; Cox, M.A.J.; Nandakumar, A.; Bosman, A.W.; Mes, T.; Janssen, H.M.; Bouten, C.V.C.; Baaijens, F.P.T.; Driessen-Mol, A.
Graphical abstract: Abstract: The emerging field of in situ tissue engineering (TE) of load bearing tissues places high demands on the implanted scaffolds, as these scaffolds should provide mechanical stability immediately upon implantation. The new class of synthetic supramolecular biomaterial polymers, which contain non-covalent interactions between the polymer chains, thereby forming complex 3D structures by self assembly. Here, we have aimed to map the degradation characteristics of promising (supramolecular) materials, by using a combination of in vitro tests. The selected biomaterials were all polycaprolactones (PCLs), either conventional and unmodified PCL, or PCL with supramolecular hydrogen bonding moieties (either 2-ureido-[1H]-pyrimidin-4-one or bis-urea units) incorporated into the backbone. As these materials are elastomeric, they are suitable candidates for cardiovascular TE applications. Electrospun scaffold strips of these materials were incubated with solutions containing enzymes that catalyze hydrolysis, or solutions containing oxidative species. At several time points, chemical, morphological, and mechanical properties were investigated. It was demonstrated that conventional and supramolecular PCL-based polymers respond differently to enzyme-accelerated hydrolytic or oxidative degradation, depending on the morphological and chemical composition of the material. Conventional PCL is more prone to hydrolytic enzymatic degradation as compared to the investigated supramolecular materials, while, in contrast, the latter materials are more susceptible to oxidative degradation. Given the observed degradation pathways of the examined materials, we are able to tailor degradation characteristics by combining selected PCL backbones with additional supramolecular moieties. The presented combination of in vitro test methods can be employed to screen, limit, and select biomaterials for pre-clinical in vivo studies targeted to different clinical applications.